Research progress in the role and mechanism of Leucine in regulating animal growth and development - Rehman, Shahab Ur; Ali, Rahmat; Zhang, Hao; Zafar, Muhammad Hammad; Wang, Mengzhi (Frontiers in Physiology, 2023)
Leucine, a branched-chain amino acid, is essential in regulating animal growth and development.Recent research has uncovered the mechanisms underlying Leucine's anabolic effects on muscle and other tissues, including its ability to stimulate protein synthesis by activating the mTORC1 signaling pathway. The co-ingestion of carbohydrates and essential amino acids enhances Leucine's anabolic effects. Moreover, Leucine has been shown to benefit lipid metabolism, and insulin sensitivity, making it a promising strategy for preventing and treating metabolic diseases, including type 2 diabetes and obesity. While emerging evidence indicates that epigenetic mechanisms may mediate Leucine's effects on growth and development, more research is needed to elucidate its mechanisms of action fully. Specific studies have demonstrated that Leucine promotes muscle growth and metabolic health in animals and humans, making it a promising therapeutic agent. However, it is essential to note that Leucine supplementation may cause digestive issues or interact with certain medications, and More study is required to determine definitively optimal dosages. Therefore, it is important to understand how Leucine interacts with other nutrients, dietary factors, and lifestyle habits to maximize its benefits. Overall, Leucine's importance in human nutrition is far-reaching, and its potential to prevent muscle loss and enhance athletic performance warrants further investigation.